NMDA Receptor-Mediated Neuroprotective Effect of the Scutellaria baicalensis Georgi Extract on the Excitotoxic Neuronal Cell Death in Primary Rat Cortical Cell Cultures - Jinsong Yang; Xiaohong Wu; Haogang Yu; Xinbiao Liao; Lisong Teng (The Scientific World Journal)
The objective of the current research work was to evaluate the neuroprotective effect of the ethanol extract of Scutellaria baicalensis (S.B.) on the excitotoxic neuronal cell death in primary rat cortical cell cultures. The inhibitory effects of the extract were qualitatively and quantitatively estimated by phase-contrast microscopy and lactate dehydrogenase (LDH) assays. The extract exhibited a potent and dose-dependent inhibition of the glutamate-induced excitotoxicity in the culture media. Further, using radioligand binding assays, it was observed that the inhibitory effect of the extract was more potent and selective for the N-methyl-D-aspartate (NMDA) receptor-mediated toxicity. The S.B. ethanol extract competed with [3H] MDL 105,519 for the specific binding to the NMDA receptor glycine site with 50% inhibition occurring at 35.1 μg/mL. Further, NMDA receptor inactivation by the S.B. ethanol extract was concluded from the decreasing binding capability of [3H]MK-801 in the presence of the extract. Thus, S.B. extract exhibited neuroprotection against excitotoxic cell death, and this neuroprotection was mediated through the inhibition of NMDA receptor function by interacting with the glycine binding site of the NMDA receptor. Phytochemical analysis of the bioactive extract revealed the presence of six phytochemical constituents including baicalein, baicalin, wogonin, wogonoside, scutellarin, and Oroxylin A.